A multinational cohort study uncovered sex differences in excess mortality after kidney transplant - Vinson, Amanda J.; Zhang, Xun; Dahhou, Mourad; Süsal, Caner; Döhler, Bernd; Melk, Anette; Sapir-Pichhadze, Ruth; Cardinal, Heloise; Wong, Germaine; Francis, Anna; Pilmore, Helen; Foster, Bethany J. (Kidney international, 2023)
Worldwide and at all ages, males have a higher mortality risk than females. This mortality bias should be preserved in kidney transplant recipients unless there are sex differences in the effects of transplantation. Here we compared the excess risk of mortality (risk above the general population) in female versus male recipients of all ages recorded in three large transplant databases. This included first deceased donor kidney transplant recipients and accounted for the modifying effects of donor sex and recipient age. After harmonization of variables across cohorts, relative survival models were fitted in each cohort separately and results were combined using individual patient data meta-analysis among 466,892 individuals (1988-2019). When the donor was male, female recipients 0-12 years (Relative Excess Risk 1.54, 95% Confidence Interval 1.20-1.99), 13-24 years (1.17, 1.01-1.34), 25-44 years (1.11, 1.05-1.18) and 60 years and older (1.05, 1.02-1.08) showed higher excess mortality risks than male recipients of the same age. When the donor was female, the Relative Excess Risk for those over 12 years were similar to those when the donor was male. There is a higher excess mortality risk in female than male recipients with differences larger at younger than older ages and only statistically significant when the donor was male. While these findings may be partly explained by the known sex differences in graft loss risks, sex differences in the risks of death with graft function may also contribute. Thus, higher risks in females than males suggest that management needs to be modified to optimize transplant outcomes among females.
Online verfügbar: 19. Februar 2023, Artikelversion: 18. Mai 2023
Gesehen am 15.08.2023